If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3f + -9 = -3 Reorder the terms: -9 + 3f = -3 Solving -9 + 3f = -3 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 3f = -3 + 9 Combine like terms: -9 + 9 = 0 0 + 3f = -3 + 9 3f = -3 + 9 Combine like terms: -3 + 9 = 6 3f = 6 Divide each side by '3'. f = 2 Simplifying f = 2
| 3(x+3)/8=5x+15 | | -9h-12=8-3h | | x^2+3x-504=0 | | 1/2(16y-40)=60 | | 70/a=10 | | 4(x+6)-3=4 | | x^2-(xy-y)= | | 4(x+6)-3whenx=4 | | 6x-15=14x-37 | | a-68=3 | | 3(x+2)-9=0 | | h-d=2 | | s*6=36 | | -2x+7=3x+5 | | 14x+25=5x | | n+15=10 | | 4w+8x-11y+2w+3x+2y= | | 8+6+74= | | 3(u-1)=-2u-8 | | 4(c-8)=12 | | 5x+7=6x+3 | | 3x+10+4=14+3x-2 | | 2x-2=28 | | 4(x-5)=16-2x | | -2w+1=-3 | | -1/3x^2-x+3=0 | | x+2=3x+12 | | 21/2+1/3-11/4 | | -4x+4/5=-3/2-2/5 | | x=21+5x | | 21+5x=x | | 12-8x=156-36x |